PENGARUH KARAKTERISTIK SOSIAL DEMOGRAFI DAN FASILITAS RUMAH DALAM PENENTUAN RUMAH TANGGA MISKIN DI PROVINSI D.I. YOGYAKARTA TAHUN 2011 (Analisis Data Susenas 2011) - , Eep Saripudin ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One important aspect to support the poverty reduction strategy is the monitoring of the poverty itself regularly and systematically in order to monitor the condition of public welfare as an early warning system. Monitoring poverty effectively be able to detect signals declining welfare, so that the authorities are able to take action on target and on time to prevent further deterioration of the condition of public welfare. Therefore, the availability of poverty data is accurate and up to date to the household level becomes very important. Measuring poverty with basic needs approach has three major disadvantages. One disadvantage is related to the concept, that poverty is conceptualized as an inability to meet basic needs and only measured in terms of per capita expenditure. This weakness is inherent in the measurement of absolute poverty, because poverty is essentially only in terms of economic inability to meet basic needs or specific standards, whereas poverty is very complex and has many social and cultural dimensions. The measurement of poverty, not only in terms of full income and expenditure only. Welfare is usually measured by the monetary dimension, however well-being can also be measured through non-monetary dimensions. Non-monetary dimensions of poverty can be seen from the opportunity to obtain health and longevity, knowledge and skills opportunities and others. The bottom line is poverty is strongly associated with the limited opportunities in determining a person's choices in life. This study aims to look at non-monetary dimensions of poverty, which is to see the influence of social characteristics, demographic and household facilities in the determination of poor households in D.I. Yogyakarta Province based on data Susenas 2011.